False Positive Results of Carpal tunnel syndrome in Electro Diagnosis Tests - MR Emad (Armaghane Danesh Bimonthly Journal, 2010)
Introduction & Objective: Carpal tunnel syndrome is identified due to compression of median nerve at wrist and develops symptoms such as wrist pain, paresthesia, numbness and the dysfunction of the hands. The gold standard to diagnose, determining prognosis and planning treatment process based on the severity of nerve involvement are electro-diagnosis tests. The purpose of this study was to specify the least and the most false positive results in common electro-diagnosis tests.